2019
DOI: 10.11591/ijece.v9i4.pp3130-3138
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial free space optical communications in Bangladesh: transmission channel characterization

Abstract: This research work focused on transmission channel characterization of Free-Space-Optical (FSO) communications technology for deploying in the developing country like Bangladesh. To meet the tremendous amount of data traffic, mobile operators and ISPs need better solution than the existing RF and fiber optic communications. Moreover, Bangladesh is entering in the era of satellite communications by launching its own satellite.  So, Bangladesh needs such communication technology that provides higher channel band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The study conducted by Haider et al has studied the impact of rain on the feasibility of FSOC links in Bangladesh. Seven cities of Bangladesh namely, Dhaka, Rajshahi, Chittagong, Sylhet, Rangpur, Mymensingh and Barisal have been considered for this study (Shahiduzzaman et al 2019). The meteorological data related to rainfall intensity of all locations from January, 2013 to June, 2016 have been collected from Bangladesh Meteorological Department.…”
Section: Related Workmentioning
confidence: 99%
“…The study conducted by Haider et al has studied the impact of rain on the feasibility of FSOC links in Bangladesh. Seven cities of Bangladesh namely, Dhaka, Rajshahi, Chittagong, Sylhet, Rangpur, Mymensingh and Barisal have been considered for this study (Shahiduzzaman et al 2019). The meteorological data related to rainfall intensity of all locations from January, 2013 to June, 2016 have been collected from Bangladesh Meteorological Department.…”
Section: Related Workmentioning
confidence: 99%
“…Some geometrical coefficients like a thickness of metal and substrate; the hole diameter also the number of periodic holes and metal properties can effect on EOT spectra because the surface plasmons that will be excited by incident light is affected by changing the size of hole and it have been confirmed that any change in the size of the holes lead to a small variations in transmission efficiency and peak [11][12][13][14][15]. Je Hong provided that the transmission characteristics is a function of film thickness of metallic hole array samples which is prepared with different hole periodicity, size and shape on a silica substrate and shows highly transmission efficiency at small thickness of gold metal [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…The 2 n C , which is also dependent on the root-mean-square (RMS) wind speed and altitude of a location, is used to characterize atmospheric turbulence as weak, moderate or strong at any point in time [27][28][29][30]. Most of the results obtained in literature [6,[10][11][12][13]20,23,[31][32][33] assume arbitrary 2 n C values or estimate them based on average wind speed measurements for a particular location. In some cases, worst case scenarios of atmospheric turbulence based on the maximum values of wind speed are investigated [29,33].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the results obtained in literature [6,[10][11][12][13]20,23,[31][32][33] assume arbitrary 2 n C values or estimate them based on average wind speed measurements for a particular location. In some cases, worst case scenarios of atmospheric turbulence based on the maximum values of wind speed are investigated [29,33]. However, these measurements are based on data spanning less than 4 years.…”
Section: Introductionmentioning
confidence: 99%